PENGARUH KOMPETENSI DAN KINERJA KARYAWAN TERHADAP KEPUASAN NASABAH PEMBIAYAAN DI BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) CABANG PANGKALPINANG - RIZKI . AMALIYAH (UIN Mataram, 2021)
Sharia People's Financing Bank (BPRS) Pangkalpinang Branch as a bank synonymous with financing products with the aim of improving the welfare of the people. BPRS employees are required to have competence and professional performance in order to be able to compete with other banks in increasing customer satisfaction. The purpose of this study was to analyze the influence of competence and employee performance on customer satisfaction financing at the Sharia Rural Bank (BPRS) Pangkalpinang Branch. The type of this research is descriptive-quantitative. Furthermore, the sampling technique of this study used random sampling techniques with a total sample of 95 respondents. The data analysis techniques used were instrument test, classical assumption test, multiple linear regression test, and hypothesis testing. This study uses SPSS Version 22.0 software.The results of this study indicate that: (1) the variable competence and employee performance with the coefficient of determination has a contribution effect on the satisfaction of financing customers at BPRS Pangkalpinang Branch by 39.9%. While the remaining 60.1% is influenced by other variables which are not researched. (2) The competency and employee performance variables simultaneously influence the satisfaction of financing customers at BPRS Pangkalpinang Branch. It can be seen from Fcount 32.168> F table 3.10 with a significance level of 0.000 <0.05. (3) The competency and employee performance variables have a partial effect on financing customer satisfaction at BPRS Pangkalpinang Branch. It can be seen from the tcount value of 2.535 and 4.873> t table 1.66159, respectively, with a significance level of 0.013 and 0.000> 0.05, respectively.